A 5‐Year Follow‐Up of a Cohort of Italian Alcoholics: Hospital Admissions and Overall Survival. (29th May 2017) - Bardazzi, Gabriele; Zanna, Ines; Ceroti, Marco; Bendinelli, Benedetta; Iozzi, Adriana; Caini, Saverio; Nesi, Gabriella; Saieva, Calogero
Abstract : Background: Alcohol use disorders (AUDs), including alcohol dependence and alcohol abuse defined according to specific DSM‐IV and ICD‐10 criteria, can be potentially lethal, because they are associated with several medical and psychiatric conditions. This study aimed to describe the causes of hospitalization of a large cohort of subjects with alcohol dependence (alcoholics) enrolled in Florence (Italy) over a 5‐year follow‐up period and to evaluate the effect of hospitalization on overall survival. Methods: One thousand one hundred and thirty alcoholics, newly diagnosed from 1997 to 2001, were linked to the Regional Mortality Registry for update of vital status as of December 31, 2006, and to the Hospital Discharge electronic archives of the Regional Health System of Tuscany to verify hospital admissions (HAs) during the 5‐year postcohort enrollment follow‐up. Kaplan–Meier survival and Cox regression analyses were performed to evaluate any association of HA with overall survival. Results: A total of 3, 916 new hospitalizations occurred during the 5‐year follow‐up. Most alcoholics (70.6%) reported at least 1 new hospitalization, with a first hospitalization rate of 61.7 per 100 person‐years in the first year of follow‐up. The mean number of hospitalizations per admitted subject was 4.87 (SD 7.4), and mean length of hospital stay was 8.5 days (SD 11.3). The main causes of hospitalization were mental disorders and diseases of the digestive system, as well as accidents or violence. Among those alcoholics alive after 1 year of follow‐up, a significantly increased risk of dying in the following years could be predicted by early hospitalization in the 12 months preceding (hazard ratio [HR] 1.73; 95% confidence interval [CI] 1.15 to 2.60) or following (HR 3.59; 95% CI 2.31 to 5.61) enrollment in the cohort. Conclusions: Our results confirm the association of AUDs with several serious medical conditions. This fact may be responsible for a high impact on health resource utilization and high social costs. Early hospitalization significantly predicts vital status at 5 years. Abstract : The figure shows the survival curves for 1, 094 newly diagnosed alcoholics alive at the end of 1st year of follow‐up in the Florence cohort 1997 to 2001, according to new Hospital Admissons (HA) occurred in the 1st year of follow‐up (yes vs. no). Survival rate in the following years was lower in admitted than in never‐admitted alcoholics (84.7% vs. 95.8%; p =0.0001), with an increased risk of dying by about 3.5 times, showing that early hospitalization significantly predicts vital status at 5 years.